Cantharellus sikkimensis sp.nov. (Cantharellales, Agaricomycetes) from the Indian Himalayas - Das, Kanad; Hofstetter, Valerie; Chakraborty, Dyutiparna; Baghela, Abhishek; Singh, Sanjay Kumar; Buyck, Bart (Phytotaxa, 2015)
This paper describes and illustrates Cantharellus sikkimensis sp.nov. from Abies densa vegetation in the mountains of Sikkim, India. The new species is phylogenetically placed in subgenus Parvocantharellus and differs from the other species of the same subgenus in the strong contrast between the dark brown, convex pileus and the yellowish color of all other parts of the fruiting bodies. It is furthermore characterized by its very long, partly hollowing and downward broadening stipe and by the size of its spores measuring 8–9–11× 5–5.5–7 µm (n= 20, Q = 1.33–1.64–2.2 µm). Cantharellus umbonatus Deepika, Upadhyay & Reddy 2013 non Pers.: Fr. 1821, nom. inval. is shown to be unrelated and suggested to be a later synonym of C. pseudoformosus. The systematic position of this species is here corrected as being member of Cantharellus subg. Cantharellus sect. Amethystini.